Cosmological correlators at the loop level - Zhehan Qin (Journal of High Energy Physics, 2025)
Abstract Cosmological correlators encode rich information about physics at the Hubble scale and may exhibit characteristic oscillatory signals due to the exchange of massive particles. Although many 1-loop processes, especially those that break de Sitter (dS) boosts, can generate significant leading signals for various particle models in cosmological collider physics, the precise results for these correlators or their full signals remain unknown due to the lack of symmetry. In this work, we apply the method of partial Mellin-Barnes (PMB) representation to the calculation of cosmological correlators at the loop level. As a first step, we use the PMB representation to calculate four-point cosmological correlators with bubble topology. We find that both the nonlocal and local signals arise from the factorized part, validating the cutting rules proposed in previous work, and are free from ultraviolet (UV) divergence. Furthermore, the UV divergence originates solely from the background piece and can be manifestly canceled by introducing the appropriate counterterm, similar to the procedure in flat spacetime. We also demonstrate how to renormalize the 1-loop correlators in Mellin space. After a consistency check with known results for the covariant case, we provide new analytical results for the signals generated from a nontrivial dS-boost-breaking bubble.